Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41589-022-01121-4
|View full text |Cite
|
Sign up to set email alerts
|

An RNA aptamer that shifts the reduction potential of metabolic cofactors

Abstract: The discovery of ribozymes has inspired exploration of RNA’s potential to serve as primordial catalysts in a hypothesized RNA world. Modern oxidoreductase enzymes employ differential binding between reduced and oxidized forms of redox cofactors to alter cofactor reduction potential and enhance the enzyme’s catalytic capabilities. The utility of differential affinity has been underexplored as a chemical strategy for RNA. Here we show an RNA aptamer that preferentially binds oxidized forms of flavin over reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Crystallographic studies revealed that exogenous DFSM molecules were tightly bound to the P450 scaffold to create a bis‐center precatalytic state of artificial peroxygenase. The binding affinity of DFSM ( K d of approximately 10 −8 M) was close to that of some natural organic cofactors for their host enzymes, such as FMN or FAD, noncovalently bound to flavoenzymes ( K d <10 −10 M) [30–32] . The high affinity ensures that DFSM can generate P450 peroxygenase activity with a low stoichiometric load, similar to a natural cofactor.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Crystallographic studies revealed that exogenous DFSM molecules were tightly bound to the P450 scaffold to create a bis‐center precatalytic state of artificial peroxygenase. The binding affinity of DFSM ( K d of approximately 10 −8 M) was close to that of some natural organic cofactors for their host enzymes, such as FMN or FAD, noncovalently bound to flavoenzymes ( K d <10 −10 M) [30–32] . The high affinity ensures that DFSM can generate P450 peroxygenase activity with a low stoichiometric load, similar to a natural cofactor.…”
Section: Discussionmentioning
confidence: 74%
“…The binding affinity of DFSM (K d of approximately 10 À 8 M) was close to that of some natural organic cofactors for their host enzymes, such as FMN or FAD, noncovalently bound to flavoenzymes (K d < 10 À 10 M). [30][31][32] The high affinity ensures…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rich suite of chemical transformations is made possible through the agency of cofactors bound to protein enzymes, and our results extend the transformations possible with ribozyme-cofactor complexes. This adds to the growing lines of evidence that as-yet-discovered RNA-cofactor pairs could catalyze a wider range of chemistries than currently known 52,53 .…”
Section: Discussionmentioning
confidence: 81%
“…It is possible that flavin was among the first cofactors used by RNAs to perform complex chemistries, following the RNA world hypothesis. This is hinted by the recent discovery of an RNA aptamer that modulates flavin’s reduction potential . Since ribozymes with SAM-dependent methylation activity , were recently discovered, it is tempting to speculate that ancient ribozymes might have used a flavin carbinolamine (similar to TrmFO and ThyX) for methylation during the early phases of life on Earth.…”
Section: Discussionmentioning
confidence: 99%